Analysis of Foodborne Outbreaks in Kenitra Province (Morocco) in 2025: Trends, Risk Factors, and Implications for Food Safety (Bangladesh Journal of Medical Science, 2025)
Background This retrospective and descriptive study aims to analyze cases of foodborne outbreaks that occurred in Kenitra province during 2025, based on information collected from the Emergency Department of Zamouri Hospital, Kenitra. In addition, a joint investigation was carried out by a multidisciplinary team from the Delegation of Health and Social Protection (including the Provincial Epidemiology Unit and the Provincial Environmental Hygiene Unit).Aim The objectives of the investigation were as follows: Confirm the existence of a foodborne outbreak (FBO); Describe the episode (timeframe, location, number of cases, severity…); Identify the source(s) of contamination and Implement appropriate management measures to control the epidemic episode and prevent further cases.Method This study seeks to identify trends and risk factors associated with these outbreaks. Data were collected from the affected patients, with particular attention paid to sex, age, and place of occurrence, while classifying cases by season to detect possible variations. In total, 71 cases of foodborne intoxications were recorded, with a strong concentration during the summer (71 cases), while winter and spring reported only 7 and 6 cases respectively.Results No cases were recorded in the autumn. Results show that men experienced a higher incidence of foodborne intoxications than women. Moreover, minors had an average of 3.692 cases, higher than adults, who averaged 2.769. It is also noteworthy that 69.231% of cases occurred at home, representing 9 out of 13 total cases. These results highlight an increased incidence of foodborne intoxications in summer, mainly at home. The analysis also reveals gender and age differences, showing that minors are more affected than adults.Conclusion These findings call for strengthened household food safety and awareness campaigns targeting vulnerable populations.BJMS, Vol. 24 No. 04 October’25 Page : 1208-1214